THE OPERATIONAL ACTIVITIES OF ENGLISH DOCUMENTS IN INTERNATIONAL OFFICE AT UNIVERSITAS NEGERI MAKASSAR - Dwina Audhyllah; Fatimah Hidayahni Amin; Indrawaty Asfah (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2023)
This research is descriptive research that aims to identify employee activities in working on international cooperation documents in English and to find out employee perceptions in making documents in the Cooperation and Public Relations section of Makassar State University. This study uses a qualitative method. This research data was collected through interviews, documents, questionnaires. The study's findings revealed that employees' activities when working on English documents were centered on the writing component, which conceptualized and wrote the document's contents, compiled and emphasized organizational ideas, searched for meaning and matched the appropriate vocabulary, corrected and re-checked English grammar, and improved the document mechanism.The researcher found that to reconfirm the use of grammar they used an application, and when they wanted to send documents or e-mails they checked again. The writing mechanism is not a problem because the format is available, so the university only manages which sentences to use and not in the cooperation document.